ANALISIS KUALITAS GARAM LOKAL DI DESA KOLAKA KECAMATAN TANJUNG BUNGA KABUPATEN FLORES TIMUR - Yosephina Margaretha Jawa Batafor; Donata Peni (JURNAL PERIKANAN TROPIS, 2025)
East Flores possesses abundant raw materials for salt production and is recognized as one of Indonesia’s key salt-producing regions. However, salt produced through traditional methods in this area has yet to meet national quality standards. This study aimed to evaluate the organoleptic and physicochemical properties of traditionally produced salt from Kolaka, Tanjung Bunga District, East Flores Regency. Salt samples were collected from traditional markets in East Flores using purposive sampling. Organoleptic assessment (aroma and color) and chemical analysis were conducted, with results compared against the Indonesian National Standard (SNI) for consumable salt. Organoleptic evaluation indicated that the salt corresponded to quality grade K3. Chemical analysis revealed that moisture content and water-insoluble matter did not comply with SNI requirements. Nevertheless, arsenic levels were below the maximum limit, confirming that the salt is safe for human consumption